Persepsi Anak terhadap Keharmonisan Orang Tua dan Kemandirian Anak - Chairiyati, Lisa Ratriana (Bina Nusantara University, 2010)
This reseach was conducted to learn the connection between children’s perception toward parents harmonic relationship and children independence on junior high school in Bekasi. The research planning is correlation with samples of 100 active students in extracurricular program. The data is gathered in cluster random sampling technique using questionnaire. This research uses 2 instruments, that are parents harmony scale and children’s independence scale. Next, data analysis is done to 100 research respondents using correlation statistic calculation of Product Moment Pearson in significancy rate 0,05 which entered into computer program of SPSS 15.0 for Windows. From data analysis came statistic descriptive which shows that children’s perception is between 6,00-8,00 score, means that according to the children, parents’ relationships are quite harmony to harmonious. Meanwhile, children’s perception about parents’ harmonious relationship has 5,80-8,00 score; which concluded that there is connection between children’s perception about parents’ harmonious relationship with children’s independency at school, where the more harmony the parents are the more independent the children are.